Administrative Errors With Potential to Harm State Finances Based on Legal Audit By The State Prosecutor - Pribadi, R. Iman; Widhiana Suarda, I Gede; Efendi, Aan (Universitas Ekasakti, 2024)
Corruption crimes in government procurement of goods and services, such as bribery, price mark-ups, and manipulation of bidding processes, can disrupt good governance, cause financial losses to the state, and diminish public trust in the government. Therefore, legal audits by the State Prosecutor play a crucial role in preventing financial losses to the state and identifying administrative errors that potentially harm state finances based on the results of such legal audits. The research findings indicate that the legal audit by the State Prosecutor in avoiding financial losses to the state through the Prosecution is governed by the Cooperation Agreement between the Ministry of Home Affairs, the State Prosecutor, and the Indonesian National Police. This audit involves receiving reports or complaints from the public, verifying with supporting evidence, providing written notices of handling outcomes, and protecting the identity of the reporters. The steps of the legal audit include ensuring objectives, planning, data confidentiality, document collection and analysis, report preparation, result exposition, and result delivery to the applicants. These stages also involve auditing findings analysis, compliance evaluations, decision feasibility assessments, and considerations for further legal actions, all aimed at maintaining integrity and accountability in governance. The State Prosecutor uses legal audits to ensure legal compliance and identify errors that could harm state finances. They determine indications of criminal acts or legal violations and assess sufficient evidence to support allegations of violations. During the audit process, the State Prosecutor looks for irregularities or legal non-compliance related to public fund management, financial misconduct, and other administrative violations involving state finances.